ALTERNATIVE LEARNING OF THE FUTURE BASED ON VERBAL-LINGUISTIC, AND VISUAL-SPATIAL INTELLIGENCE THROUGH YOUTUBE-BASED MIND MAP WHEN PANDEMIC COVID-19 - Aan Yuliyanto; Rifqi Abdul Basit; Idat Muqodas; Hayani Wulandari; Dinda Mifta Amalia (Universitas Ahmad Dahlan, 2020)
ABSTRAKKecerdasan menggambarkan kemampuan individu menyelesaikan tugas untuk mencapai tujuan. Perkembangan jaman turut mengembangkan temuan baru diantaranya kecerdasan jamak yang dicetuskan Howard Gardner terdiri sembilan kecerdasan. Dalam kajian literatur ini akan membahas pengembangan kecerdasan visual-spasial dan kecerdasan verbal-lnguistik siswa dengan mind map berbantuan youtube untuk menunjang alternatif pembelajaran masa depan setelah munculnya COVID-19. Mind map dianggap cocok untuk mengembangkan kecerdasan visual spasial dan kecerdasan verbal-linguistik karena pembelajaran mind map berhubungan dengan gambar, warna, kata-kata yang sesuai dengan indikator kecerdasan visual-spasial dan kecerdasan verbal-linguistik, media youtube membantu siswa mengembangkan topik yang dibahas serta menunjang kecerdasan dalam pembelajaran jarak jauh ditengah pandemi COVID-19. Dengan demikian penelitian ini sebagai solusi gambaran pembelajaran jarak jauh untuk pengembangan kecerdasan jamak ditengah pandemi COVID-1.ABSTRACTIntelligence describes the ability of individuals to complete tasks to achieve goals. Development of the times helped develop discoveries including multiple intelligences that Howard Gardner coined consisted of nine intelligences. This literature review will discuss the development of visual-spatial intelligence and the verbal-linguistic intelligence of students with a YouTube-assisted mind map to support future learning alternatives after the advent of COVID-19. The mind map is considered suitable for developing spatial-visual intelligence and verbal-linguistic intelligence because mind map learning is related to images, colors, words that are following indicators of visual-spatial intelligence and verbal-linguistic intelligence, YouTube media helps students develop topics discussed and support intelligence in distance learning amid the COVID-19 pandemic. Thus, this study as a solution to the description of distance learning for the development of multiple intelligences amid the COVID-19 pandemic.